Endemic or introduced? Phylogeography of Asparagopsis (Florideophyceae) in Australia reveals multiple introductions and a new mitochondrial lineage - Andreakis, Nikos; Costello, Paul; Zanolla-Balbuena, Maríanela Fernanda; Saunders, Gary W.; Mata, Leonardo (Wiley Online Library, 2015)
The red seaweed Asparagopsis taxiformis represents an iconic species complex of five mitochondrial lineages (lineage 1 to 5) introduced worldwide as a consequence of human mediated transport and climate change. Here we compare globally collected mitochondrial cox2-3 intergenic spacer sequences against sequences produced from multiple Australian locations and South Korea to identify Asparagopsis lineages and to reveal cryptic introductions. We report A. taxiformis lineage 4 from Cocos (Keeling) Islands, Australia, and the highly invasive Indo-Pacific Mediterranean lineage 2 from South Korea and Lord Howe Island, Australia. Phylogeographic analysis showed a clear haplotype and geographic separation between western Australian and Great Barrier Reef (GBR) isolates belonging to the newly described A. taxiformis lineage 5. The same lineage however, was characterized by a substantial genetic and geographical break between the majority of Australian specimens and Asparagopsis collections from South Solitary Island, Southern GBR, Lord Howe Island, Kermadec Islands, Norfolk Island, New Caledonia and French Polynesia. The distinct geographical distribution and the amount of diversification between these two groups justify the establishment of a sixth A. taxiformis mitochondrial cryptic lineage.
Keywords: Especies exóticas invasoras; Asparagopsis; Australia; GBR; Invasive species; Phylogeography; Invasive; Endemic; Cryptic